288What proportion of patients with chronic noncancer pain are prescribed an opioid medicine?. (2nd September 2021) - Mathieson, Stephanie; Wertheimer, Graeme; Maher, Christopher G; Lin, Christine; McLachlan, Andrew J; Buchbinder, Rachelle; Pearson, Sallie-Anne; Underwood, Martin
Abstract: Background: Guidelines now discourage opioid analgesics for chronic non-cancer pain because the benefits frequently do not outweigh the harms. This review determined the proportion of patients with chronic non-cancer pain who are prescribed an opioid, the types prescribed, and factors associated with prescribing. Methods: Database searches were conducted from inception to 29 th October 2018 without restrictions. We included observational studies of adults with chronic non-cancer pain measuring opioid prescribing. Opioids were categorised as weak (e.g. codeine) or strong (e.g. oxycodone). Risk of bias assessed study quality. Results were pooled using a random-effects model. Meta-regression investigated study-level factors associated with prescribing. The overall evidence quality was assessed using GRADE criteria. Results: Of the 42 studies (5, 059, 098 participants) included, majority (n = 28) from the United States of America. Eleven studies were at low risk of bias. The pooled estimate of the proportion of patients with chronic non-cancer pain prescribed opioids was 30.7% (95%CI 28.7% to 32.7%, 42 studies, moderate-quality evidence). Strong opioids were more frequently prescribed than weak (18.4% (95%CI 16.0% to 21.0%, n = 15 studies, low-quality evidence), versus 8.5% (95%CI 7.2% to 9.9%, n = 15 studies, low-quality evidence)). Meta-regression determined opioid prescribing was associated with year of sampling (more prescribing in recent years) (p = 0.014) and not geographic region (p = 0.056). Conclusions: Opioid prescribing for patients with chronic non-cancer pain is common and has increased over time. Key message: Opioid prescribing for patients with chronic non-cancer pain and has increased over time. This review is the first systematic review to synthesized such data.